Salmonella osteomyelitis in aplastic anaemia after antilymphocytic globulin and steroid treatment. Issue 2 (February 1992) - Allard, S; O'Driscoll, J; Laurie, A
Abstract : A 22 year-old patient with severe aplastic anaemia responded to antilymphocytic globulin but developed recurrent fever despite treatment with steroids and then antibacterial, antifungal, and antituberculous drugs. There was progression, with severe joint pains and immobility associated with radiological evidence of a symmetrical destructive process. A bone marrow specimen showed no evidence of malignancy, and cultures of blood, urine, and stool were negative but enriched broth cultures of an open biopsy specimen of the humeral head grew Salmonella enteritidis phage type 4. Treatment with ciprofloxacin resulted in considerable symptomatic improvement: a total of 12 months of treatment is planned. Salmonella osteomyelitis, particularly with this unusual pattern of disease, has not previously been described in aplastic anaemia.